2010
DOI: 10.1177/1359786810382056
|View full text |Cite
|
Sign up to set email alerts
|

Review: Do deficits in cardiac care influence high mortality rates in schizophrenia? A systematic review and pooled analysis

Abstract: We have previously documented inequalities in the quality of medical care provided to those with mental ill health but the implications for mortality are unclear. We aimed to test whether disparities in medical treatment of cardiovascular conditions, specifically receipt of medical procedures and receipt of prescribed medication, are linked with elevated rates of mortality in people with schizophrenia and severe mental illness. We undertook a systematic review of studies that examined medical procedures and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(68 citation statements)
references
References 88 publications
(118 reference statements)
4
59
1
1
Order By: Relevance
“…Our results concerning coronary mortality, hospitalisations and revascularisation procedures are in line with those reported from studies examining total populations of persons with specific severe mental disorders1 9 13 14 and our results replicate especially the low hospital admission rates and revascularisation rates among persons with psychosis in relation to need indicated by excess coronary mortality 16. Some studies have reported no differences in hospitalisations or revascularisations, but these studies have been based on clinical coronary populations and not total populations of persons with severe mental disorders,30–32 whereas our study covered the total population of persons with mental disorders severe enough to require hospitalisation.…”
Section: Discussionsupporting
confidence: 90%
“…Our results concerning coronary mortality, hospitalisations and revascularisation procedures are in line with those reported from studies examining total populations of persons with specific severe mental disorders1 9 13 14 and our results replicate especially the low hospital admission rates and revascularisation rates among persons with psychosis in relation to need indicated by excess coronary mortality 16. Some studies have reported no differences in hospitalisations or revascularisations, but these studies have been based on clinical coronary populations and not total populations of persons with severe mental disorders,30–32 whereas our study covered the total population of persons with mental disorders severe enough to require hospitalisation.…”
Section: Discussionsupporting
confidence: 90%
“…Due to limitations of our dataset, we could not determine the "appropriateness" of the use of revascularization in any of our patients, but this treatment difference persisted after adjusting for differences in coronary anatomy. Some have suggested that this treatment disparity, and lack of access to appropriate treatment of CVD more broadly, may be a contributing factor to the premature mortality seen among those with schizophrenia [22,23]. Our findings do not support this.…”
Section: Discussioncontrasting
confidence: 85%
“…Inequalities in disease management for individuals with mental illnesses have been reported in the literature and range from suboptimal preventative medical care (29) to poor quality management of chronic diseases and surgical interventions (30, 31). In a meta-analysis of cardiovascular disease management, patients with severe mental illnesses were less likely to receive appropriate prescriptions for cardiovascular disease or to undergo basic cardiac procedures (31). Similarly, another study showed that individuals with mental illnesses received substandard diabetic care and had more diabetic complications(30).…”
Section: Discussionmentioning
confidence: 99%